The Relationship between Exchange Rate, Money Supply, and Inflation in Indonesia: An ARDL Approach: English - Sari, Refika Cyntia; Popy Ridhona Tambunan; Muhammad Syahru Ramadhana (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2025)
This study examines the short- and long-term relationships between inflation, exchange rate, and money supply (M2) in Indonesia using the Autoregressive Distributed Lag (ARDL) approach over the period 2013–2024. Monthly time-series data obtained from official sources are analyzed to capture the dynamic interactions among variables. The bounds testing procedure confirms the existence of a long-run cointegration relationship, with the ARDL(5,1,2) model identified as the optimal specification. Empirical results indicate that, in the short run, inflation is significantly influenced only by its own past values, while the exchange rate and money supply are statistically insignificant in both the short and long term. These findings suggest that inflation dynamics in Indonesia are primarily driven by internal adjustment mechanisms rather than direct monetary or exchange rate shocks. The study contributes to monetary policy analysis by highlighting the importance of inflation expectations and domestic stability.